2004
DOI: 10.1089/152308604773934350
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Oxygenation in Intracellular and Extracellular Compartments of Lung Microvascular Endothelial Cells

Abstract: A new technique is described for simultaneous determination of intra- and extracellular oxygen concentrations [partial pressure of O(2) (pO(2))] in bovine lung microvascular endothelial cells (BLMVECs) using electron paramagnetic resonance (EPR) oximetry. The measurements were performed in BLMVEC suspensions of a 20- micro l volume containing 4,000 cells. The extracellular pO(2) was measured using a trityl EPR probe [triarylmethyl (TAM), 10 micro M], a tricarboxylate anion radical, that stays exclusively in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…For example, although a 10-fold difference in signal-to-noise ratio occurred to the experimental spectra (corresponding to 100 times difference in microwave power), accurate linewidth information has been still achieved through curve fitting. These linewidths obtained at different concentrations are consistent with the previously reported values [9,22,24]. Table 1 summarizes the linewidth information of LiNc-BuO at different oxygen concentrations and different microwave power levels.…”
Section: Resultssupporting
confidence: 89%
“…For example, although a 10-fold difference in signal-to-noise ratio occurred to the experimental spectra (corresponding to 100 times difference in microwave power), accurate linewidth information has been still achieved through curve fitting. These linewidths obtained at different concentrations are consistent with the previously reported values [9,22,24]. Table 1 summarizes the linewidth information of LiNc-BuO at different oxygen concentrations and different microwave power levels.…”
Section: Resultssupporting
confidence: 89%
“…SMs were isolated from the hindlimb skeletal muscle biopsies of mice and cultured as described previously (42). The cells were coincubated with a suspension of sonicated OxySpin crystals for 48 h (15,42). We have recently reported that myoblasts labeled with or coincubated in the presence of OxySpin probes did not show any significant change in viability, metabolism, or proliferation rate (42 …”
Section: Methodsmentioning
confidence: 99%
“…The particulate probes measure PO 2 in the tissue milieu. Lithium octa-n-butoxy-substituted naphthalocyanine radical (LiNc-BuO) is a particulate oximetry spin probe that we have recently synthesized and validated for in vivo oximetry (2,15,27,42,43). The LiNc-BuO crystals are composed of stacks of neutral radicals of lithiated naphthalocyanine macrocycles (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Once implanted, the probe responds to PO 2 in the immediate surrounding, mostly at the crystal-tissue interface, enabling magnetic resonance-based noninvasive and repeated measurements of PO 2 for a prolonged period from the site of implantation. The technology has been well validated for measurements of PO 2 from single cells to whole organs (16,26,38).…”
Section: Induction Of Myocardial I/r In Vivomentioning
confidence: 99%